2018
DOI: 10.1590/s1678-86212018000400297
|View full text |Cite
|
Sign up to set email alerts
|

Consumo energético de salas de escritório climatizadas de modo misto em São Paulo: considerações sobre o projeto

Abstract: Resumo Na literatura há poucos estudos sobre edifícios climatizados de modo misto (ou com ventilação híbrida) com estratégias simples de projeto. Dessa forma, esta pesquisa avalia o impacto de parâmetros arquitetônicos (formato da sala, tamanho e orientação das aberturas) e de uso (densidade de carga de equipamentos e temperatura de acionamento do ar-condicionado) no desempenho energético de salas de escritório de modo misto na cidade de São Paulo. O método consistiu em um levantamento de dados dessa tipologia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The study indicated the window frames as important feature in the building’s performance. Santesso and Chvatal 57 performed a similar study for mixed-use office building located in São Paulo. The results verified the importance of associating the room dimension and the WWR.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated the window frames as important feature in the building’s performance. Santesso and Chvatal 57 performed a similar study for mixed-use office building located in São Paulo. The results verified the importance of associating the room dimension and the WWR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results verified the importance of associating the room dimension and the WWR. 57 The complex relation of geometric design with buildings’ thermal and energy performance led to recent multi-objective studies that associate the buildings’ shape parameterization. Santana 50 carried out a multi-objective optimization of a residential building based on the PBE Edifica [Brazilian Labelling Program for Buildings] requirements.…”
Section: Literature Reviewmentioning
confidence: 99%